Effects of nitrogen, phosphorus and potassium levels on kenaf (Hibiscus cannabinus L.) growth and photosynthesis under nutrient solution - Hossain, Md. Delwar; Musa, Mohamed Hanafi; Talib, Jamal; Jol, Hamdan (Canadian Center of Science and Education, 2010)
To date, little is known about the effect of levels of nitrogen, phosphorus and potassium on kenaf grown in nutrient solution culture. The objective of the present study was to examine the effects of different nitrogen, phosphorus and potassium levels on kenaf growth such as diameter, plant height, leaf number, root dry weight, stem dry weight and leaf dry weight and physiology like chlorophyll content, photosynthesis and stomatal conductance. Treatment consisted of 5 different levels of nitrogen viz. 0, 50, 100, 200 and 400 mg/L and 5 different levels of phosphorus and potassium viz. 0, 25, 50, 100 and 200 mg/L replicated thrice in a completely randomized design in a shade house. Growth (diameter, plant height and leaf number), chlorophyll content and photosynthesis were measured once weekly and plant components biomass was measured, 28 DAT. Different levels of nitrogen, phosphorus and potassium had significant effects on all the parameters studied. The highest values for diameter, plant height, leaf number, root dry weight, stem dry weight, leaf dry weight, photosynthesis and stomatal conductance were obtained from 200N, 100P and 100K whereas values decreased with further increase in levels of nutrient concentration. All the growth rates, chlorophyll content and photosynthesis declined with lower level of nitrogen, phosphorus and potassium. Among the plant components, leaf dry weight had the greatest decrease while root/shoot ratio increased under N deficiency. The results of this study provide new knowledge to produce kenaf with better nutrient management in the field.